2013
DOI: 10.1128/aac.00452-13
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal–α-Amino Acid Complexes with Antibiotic Activity against Mycobacterium spp

Abstract: Synthetic iridium-, rhodium-, and ruthenium-amino acid complexes with hydrophobic L-amino acids have antibiotic activity against Mycobacterium spp., including Mycobacterium bovis BCG and the rapidly growing species Mycobacterium abscessus and Mycobacterium chelonae. Concentrations of transition metal-amino acid complexes demonstrating hemolysis or cytotoxicity were 10-to 25-fold higher than were the MICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 16 publications
1
46
0
Order By: Relevance
“…One of the first Cp ⁄ metal complexes was made by reaction between IrCl 3-Á3H 2 O and hexamethyldewarbenzene [7]. A complete review of Cp ⁄ complexes would be massive, but recent publications show that Cp ⁄ may be used in complexes for transfer hydrogenation [8][9][10][11], water oxidation [12][13][14], anti-cancer activity [15,16], and antimicrobial activity [17]. The development of much early metal chemistry was made possible in large part to the use of pentamethylcyclopentadiene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first Cp ⁄ metal complexes was made by reaction between IrCl 3-Á3H 2 O and hexamethyldewarbenzene [7]. A complete review of Cp ⁄ complexes would be massive, but recent publications show that Cp ⁄ may be used in complexes for transfer hydrogenation [8][9][10][11], water oxidation [12][13][14], anti-cancer activity [15,16], and antimicrobial activity [17]. The development of much early metal chemistry was made possible in large part to the use of pentamethylcyclopentadiene.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of [(g 5 -C 5 Me 4 iPr)Ir(L-phenylalaninate)Cl] complex(17) Following the general procedure: 0.1000 g (0.173 mmol) of [(g 5 -C 5 Me 4 iPr)IrCl 2 ] 2 was combined with 0.0410 (0.246 mmol) of L-phenylalanine and 0.0207 g (0.246 mmol) of sodium hydrogen carbonate in methanol (30 mL) to produce 17, 0.1071 g (82.3% yield). 17 was identified based on the following information:Major isomer: 1 H NMR (400 MHz, CDCl 3 ) d 7.37-7.25 (m, 5H, ArH), 4.20 (br s, 1H, NH), 3.97-3.91 (m, 1H, NH), 3.87 (tt, J = 7.6, 5.2 Hz, 1H, aCH), 3.39 (dd, J = 14.3, 5.4 Hz, 1H, CH), 3.06 (dd, J = 14.3, 5.0 Hz, 1H, CH), 2.43 (sept, J = 7.1 Hz, 1H, Me 2 CH), 1.59 (s, 3H, CpMe), 1.55 (s, 3H, CpMe), 1.49 (s, 3H, CpMe), 1.48 (s, 3H, CpMe), 1.16 (overlapping doublets J = 7.1 Hz, 6H, CHMe 2 ) ppm.…”
mentioning
confidence: 99%
“…23 A review on small organometallic compounds as antibacterial agents appeared recently. 25 Herein we extend our documentation of the strong antibiotic properties of a different family of transition metal complexes containing 1,2-diamine ligands to S. aureus and MRSA. 25 Herein we extend our documentation of the strong antibiotic properties of a different family of transition metal complexes containing 1,2-diamine ligands to S. aureus and MRSA.…”
Section: Introductionmentioning
confidence: 68%
“…25 None of the amino acid compounds displayed any significant anti-staphylococcal activity. 25 None of the amino acid compounds displayed any significant anti-staphylococcal activity.…”
Section: Chemistrymentioning
confidence: 97%
“…The groups of Falkinham and Merola have previously investigated piano-stool type complexes of iridium and rhodium with amino acid ligands for their antimycobacterial activity, reporting better activity for the complexes bearing hydrophobic amino acids. The presence of a cyclopentadiene (Cp) ligand was also found to correlate with better antimycobacterial activity [100]. Follow up studies reported a series of pentaalkylcyclopentadienyl iridium and two cobalt complexes with three iridium and one cobalt compound possessing promising activity against nine S. aureus strains, including seven MRSA strains derived from patients and laboratories (24, MICs = 4-8 µg/mL, Figure 9).…”
Section: Iridiummentioning
confidence: 98%